High-conductivity pure copper busbar and preparation method thereof

CN122417545BActive Publication Date: 2026-10-09GUANGDONG RIZHAO ELECTRIC CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610735656.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-05-26
Publication Date
2026-10-09
Estimated Expiration
2046-05-26

AI Technical Summary

Technical Problem

[0009]针对现有技术中母线绝缘层导热能力不足导致铜导体温升过高、导电率衰减,界面热阻累积与应力脱粘加速老化失效,以及高导热与高绝缘、阻燃、韧性难以兼顾的技术缺陷,本发明提供一种高导电率纯铜母线及其制备方法

Benefits of technology

[0025]本发明提供的高导电率纯铜母线及其制备方法,通过无氧铜管与导热绝缘层和金属屏蔽层的设计,以及导热绝缘层中基体环氧树脂与功能超支化环氧树脂的复配、三维导热填料网络构建及动态共价交联技术的协同作用,取得了以下有益效果:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122417545B_ABST
    Figure CN122417545B_ABST
Patent Text Reader

Abstract

The application discloses a high-conductivity pure copper bus and a preparation method thereof, and belongs to the technical field of bus. The high-conductivity pure copper bus comprises an oxygen-free copper pipe, a heat-conducting insulation layer coated on the outer surface of the oxygen-free copper pipe and a metal shielding layer coated on the outer surface of the heat-conducting insulation layer. The heat-conducting insulation layer comprises, by weight, 75-100 parts of a base epoxy resin, 10-15 parts of a functional hyperbranched epoxy resin, 90-130 parts of a heat-conducting filler, 8-13 parts of a toughening agent, 1.5-4 parts of a dynamic crosslinking agent, 80-100 parts of a curing agent and 0.3-0.8 parts of a curing accelerator. The epoxy insulation layer of the pure copper bus has the effects of high heat conduction, high insulation, high flame retardation, high toughness and high interface reliability, the operating temperature rise of the copper conductor is significantly reduced, the conductivity of the bus system can be maintained for a long time, and the bottleneck that heat conduction and insulation, rigidity and toughness, flame retardation and temperature resistance are difficult to be considered simultaneously in the existing bus insulation technology is broken.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of busbar technology, specifically to a high-conductivity pure copper busbar and its preparation method. Background Technology

[0002] As the core current-carrying conductor in high-current power transmission and distribution systems, the conductivity of the busbar directly determines the power transmission efficiency and the conductor's heating level. Industrially, the conductivity of copper busbars is typically characterized by %IACS (International Annealed Copper Standard). High conductivity means lower resistance loss and lower operating temperature rise. However, the conductivity of a busbar in actual operation is not a constant value but is significantly affected by thermodynamic conditions—according to the temperature coefficient of resistance of metals, for every 1°C increase in temperature of a copper conductor, the resistance increases by approximately 0.393%, and the conductivity decreases accordingly. When the long-term operating temperature of the busbar rises from 20°C to 90°C due to poor heat dissipation, its conductivity can decrease by more than 20%, resulting in a significant reduction in its equivalent current-carrying capacity.

[0003] Therefore, the conductivity of the busbar system depends not only on the purity of the copper conductor itself, but also on the thermal conductivity and heat dissipation capacity of the insulation layer. As a thermal resistance barrier between the copper conductor and the external environment, the heat dissipation efficiency of the thermally conductive insulation layer directly determines the operating temperature of the copper tube: if the insulation layer has a low thermal conductivity and high thermal resistance, the heat generated by the copper tube cannot be dissipated in time, and the accumulated temperature rise will significantly reduce the actual conductivity of the busbar; conversely, a high thermal conductivity insulation layer can effectively reduce the operating temperature of the copper tube, allowing the busbar to maintain a high conductivity close to the nominal value throughout its entire lifespan.

[0004] Furthermore, the interfacial thermal resistance between the copper conductor and the insulation layer is also a key factor affecting the conductivity of the system. Micropores, oxide layers, or debonding cracks at the interface introduce additional contact thermal resistance. Even if the insulation layer itself has good thermal conductivity, local temperature rise at the interface can still lead to hot spots in the copper tube, creating a "weakest link" effect in conductivity. During thermal cycling, the difference in thermal expansion coefficients between copper and the insulation material will generate shear stress at the interface. After long-term operation, this can easily induce microcracks and delamination, further worsening interfacial heat transfer and accelerating conductivity decay.

[0005] In the field of thermally conductive and insulating materials, epoxy resin is widely used for busbar cladding due to its excellent electrical insulation and mechanical properties. However, ordinary epoxy resin has an extremely low intrinsic thermal conductivity, making it difficult to meet the heat dissipation requirements of high-current busbars. To improve thermal conductivity, the industry typically adds inorganic fillers such as alumina and boron nitride to the epoxy matrix. However, in existing technologies, fillers are mostly in a randomly dispersed state, especially anisotropic sheet-like or fibrous fillers, which have disordered orientation in the matrix. This results in limited improvement in the thermal conductivity outside the insulation layer, and heat is still difficult to efficiently dissipate radially along the copper tube.

[0006] Meanwhile, the introduction of high-volume-fraction fillers brings a series of process and performance contradictions: when the filler content is too high, the system viscosity increases sharply, the wettability with epoxy resin deteriorates, and casting or impregnation molding becomes difficult; the filler-resin interface defects increase, which not only reduces insulation strength but also becomes a channel for water vapor penetration, and the interface thermal resistance increases significantly after long-term humid heat aging. More challenging is that the existing epoxy insulation layer and copper conductor are mostly static rigid bonds, which cannot adapt to the dynamic changes in interface stress during thermal cycling. After long-term operation, interface debonding and crack propagation lead to insulation failure and heat dissipation deterioration, further aggravating the attenuation of busbar conductivity.

[0007] Regarding flame retardancy, epoxy resin itself is flammable, and traditional halogenated flame retardants have been gradually phased out due to environmental regulations. Excessive addition of inorganic hydroxide flame retardants can severely degrade the mechanical and electrical insulation properties of the resin. Maintaining high strength, high toughness, and high temperature resistance of the epoxy insulation layer while ensuring flame retardancy remains a challenge for the industry.

[0008] In summary, existing busbar technologies face significant technical bottlenecks in achieving a balance between maintaining high conductivity, efficient thermal conductivity of the insulation layer, long-term interface reliability, and flame retardancy and temperature resistance. Insufficient heat dissipation capacity of the thermally conductive insulation layer leads to excessive temperature rise in the copper tube and conductivity degradation; interface thermal resistance and stress accumulation accelerate aging and failure; and effective material solutions are still lacking for the synergistic realization of high thermal conductivity, high insulation, high flame retardancy, and high toughness. Therefore, there is an urgent need to develop a busbar that can simultaneously reduce insulation thermal resistance, suppress interface thermal resistance growth, and maintain low temperature rise operation of the copper conductor. Summary of the Invention

[0009] To address the shortcomings of existing technologies, such as insufficient thermal conductivity of the busbar insulation layer leading to excessive temperature rise and conductivity decay in copper conductors, accelerated aging and failure due to accumulated interfacial thermal resistance and stress debonding, and the difficulty in simultaneously achieving high thermal conductivity with high insulation, flame retardancy, and toughness, this invention provides a high-conductivity pure copper busbar and its preparation method. The core concept of this invention lies in: through the material system and structural design of the oxygen-free copper tube and thermally conductive insulation layer, significantly reducing the thermal resistance from the outer surface of the copper tube to the external environment, allowing the copper conductor to maintain a lower operating temperature under rated current carrying capacity, thereby maintaining a high conductivity close to the nominal value throughout its entire lifespan; simultaneously, through dynamic covalent interfacial bonding technology, suppressing the growth of interfacial thermal resistance during thermal cycling, ensuring the electrical safety and structural reliability of the busbar during long-term operation.

[0010] To achieve the above objectives, the present invention adopts the following technical solution: A high-conductivity pure copper busbar includes an oxygen-free copper tube, a thermally conductive insulating layer covering the outer surface of the oxygen-free copper tube, and a metal shielding layer covering the outer surface of the thermally conductive insulating layer. The thermally conductive insulating layer, by weight, includes 75-100 parts of matrix epoxy resin, 10-15 parts of functional hyperbranched epoxy resin, 90-130 parts of thermally conductive filler, 8-13 parts of toughening agent, 1.5-4 parts of dynamic crosslinking agent, 80-100 parts of curing agent, 0.3-0.8 parts of curing accelerator, and 0-6 parts of additives.

[0011] In one specific embodiment, the oxygen-free copper tube is made of oxygen-free copper with an oxygen content of no more than 20 ppm and a conductivity of no less than 99% IACS, preferably TU1 oxygen-free copper or ASTM C10200 oxygen-free high-conductivity copper with an oxygen content of no more than 10 ppm and a conductivity of no less than 100% IACS, and the wall thickness of the oxygen-free copper tube is 2~5 mm.

[0012] In one specific embodiment, the material of the metal shielding layer is at least one of aluminum and aluminum alloys, austenitic stainless steel, and copper-clad aluminum composite material, and the thickness of the metal shielding layer is 0.1~0.5mm; preferably, the inner surface of the metal shielding layer material is treated with anodizing or silane coupling agent primer to form a low thermal resistance interface with the outer surface of the thermally conductive insulating layer, and is reliably connected to the system protective ground through multi-point grounding.

[0013] In one specific embodiment, the thickness of the thermally conductive insulating layer is 2~8mm, preferably 3~5mm.

[0014] In one specific embodiment, the matrix epoxy resin is selected from one or more of bisphenol A type epoxy resin, alicyclic epoxy resin, and phenolic epoxy resin. Preferably, the matrix epoxy resin is a compound of bisphenol A type epoxy resin, alicyclic epoxy resin, and phenolic epoxy resin, with a mass ratio of (5~7):(2~3):(1~2).

[0015] In one specific embodiment, the functional hyperbranched epoxy resin is prepared by A2+B3 polymerization reaction of DOPO-itaconic anhydride-catechol diamine adduct and trifunctional epoxy monomer. The trifunctional epoxy monomer is selected from one or more of triglycidyl isocyanurate, trimethylolpropane triglycidyl ether, and tris(4-hydroxyphenyl)methane triglycidyl ether. Preferably, the trifunctional epoxy monomer is selected from triglycidyl isocyanurate.

[0016] In one specific embodiment, the DOPO-itaconic anhydride-catechol diamine adduct has the following general structural formula: , where n is a natural number between 1 and 3.

[0017] In one specific embodiment, the preparation method of the DOPO-itaconic anhydride-catechol diamine adduct includes the following steps: (1) DOPO was reacted with itaconic anhydride to prepare the DOPO-itaconic anhydride intermediate; (2) Catechol diamine was prepared by Schiff base condensation and sodium borohydride reduction of 3,4-dihydroxybenzaldehyde and C2~C6 aliphatic diamine. (3) The DOPO-itaconic anhydride intermediate and catechol diamine were amidated and condensed to obtain the DOPO-itaconic anhydride-catechol diamine adduct.

[0018] In one specific embodiment, the thermally conductive filler comprises one or more of boron nitride fibers, lamellar hexagonal boron nitride, or spherical alumina. Preferably, the thermally conductive filler comprises a compound of boron nitride fibers, lamellar hexagonal boron nitride, and spherical alumina, wherein the mass ratio of boron nitride fibers, lamellar hexagonal boron nitride, and spherical alumina is (1~2):(2~3):(6~8). The boron nitride fibers are arranged perpendicularly along the thickness direction of the thermally conductive insulating layer, working in conjunction with the dense filling phase of the spherical alumina and the in-plane thermally conductive phase of the lamellar hexagonal boron nitride to construct a three-dimensional low thermal resistance channel penetrating from the outer surface of the copper tube to the inner surface of the metal shielding layer. More preferably, the spherical alumina and lamellar hexagonal boron nitride are surface-modified with a silane coupling agent.

[0019] In one specific embodiment, the toughening agent comprises one or more of core-shell rubber particles or end-carboxyl hyperbranched polyesters; preferably, the toughening agent comprises a compound of core-shell rubber particles and end-carboxyl hyperbranched polyesters; the core-shell rubber particles or end-carboxyl hyperbranched polyesters can absorb impact energy and reduce stress concentration, thereby improving toughness while maintaining the glass transition temperature.

[0020] In one specific embodiment, the dynamic crosslinking agent includes one or more of boric acid, phenylboronic acid, or 3-carboxyphenylboronic acid; during the curing process, the dynamic crosslinking agent undergoes dehydration condensation with the 1,2-dihydroxybenzene structure of the side chain of the functional hyperbranched epoxy resin to form a 1,3,2-benzodioxaborane structure in situ, which establishes a reversible exchange equilibrium in the crosslinking network to release the thermal cycling stress at the copper-epoxy interface.

[0021] The curing agent is methylhexahydrophthalic anhydride; the curing accelerator is 2-ethyl-4-methylimidazole; the additives include one or more of defoamers or reactive diluents, wherein the reactive diluent is selected from one or more of 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, and phenyl glycidyl ether; the dosage is 3-5 parts; the defoamer is selected from one of polyether-modified polysiloxane, polyacrylate defoamer, or silicone-free polyether defoamer, and the dosage is 0.2-1.0 parts.

[0022] This invention also protects a method for preparing the high-conductivity pure copper busbar, comprising the following steps: S1. Roughen the surface of the oxygen-free copper tube to remove oxide scale and oil stains, then immerse it in an aqueous solution of aminosilane coupling agent ethanol, adjust the pH to 4.5~5.0 with acetic acid, let it stand at room temperature for a period of time, take it out and dry it to form a chemically bonded base coating. S2. Weigh the base epoxy resin, functional hyperbranched epoxy resin, thermally conductive filler and toughening agent according to the weight parts, put them into a mixer, heat to 60~80℃, vacuum, and disperse at high speed to make the filler uniformly wet and pre-disperse in the resin matrix; cool to 40~50℃, add curing agent, curing accelerator and dynamic crosslinking agent in sequence under continuous stirring, stir at low speed until dispersed, vacuum degas, and obtain thermally conductive insulating layer adhesive. S3. Immerse the oxygen-free copper tube obtained in S1 into a thermally conductive insulating layer adhesive tank to uniformly coat the outer surface of the copper tube. Place the coated copper tube into a stainless steel forming mold and place the mold horizontally. Rotate at a low speed of 10-20 rpm for 30-60 minutes. Under the coupling effect of the rotational shear field and weak centrifugal force, the thermally conductive filler is oriented in the radial-circumferential composite direction in the insulating layer. It works in conjunction with the in-plane thermally conductive phase of the plate-shaped hexagonal boron nitride and the dense filling phase of the spherical alumina to construct a three-dimensional low thermal resistance thermally conductive channel that runs through the outer surface of the copper tube to the inner surface of the metal shielding layer. Then, place the mold under 80-100℃ and ≤-0.095 MPa conditions for pre-curing and in-situ dehydration and esterification. Release the vacuum and transfer the mold to 120-150℃ for complete curing. Demold naturally to obtain an oxygen-free copper tube coated with a thermally conductive insulating layer. S4. On the outer surface of the thermally conductive insulation layer, a metal strip is spirally wrapped or a metal foil is longitudinally wrapped. The inner surface of the metal is pre-coated with an epoxy silane coupling agent. The overlap is made of conductive adhesive or argon arc spot welding. Grounding wires are led out at intervals of ≤1.5m and reliably connected to the system protective ground.

[0023] It should be noted that the low-speed horizontal rotation of the mold is not intended to ensure a strict 90° perpendicular relationship between the boron nitride fibers and the thickness direction of the insulation layer. In the high-viscosity epoxy resin system, the fibers are simultaneously subjected to the coupling effects of rotational shear force, weak centrifugal force, and the constraint of the stainless steel wall of the mold. Their long axis forms a distribution angle of 20-70° with the radial direction of the insulation layer, forming a radially deflected directional arrangement. This distribution is sufficient to construct an efficient fiber-fiber and fiber-filler contact thermal conductivity network in the thickness direction of the insulation layer, significantly reducing out-of-plane thermal resistance. Compared to a completely randomly oriented static casting system, the out-of-plane thermal conductivity of this directional arrangement structure is increased by more than 30%.

[0024] Beneficial effects

[0025] The high-conductivity pure copper busbar and its preparation method provided by this invention achieve the following beneficial effects through the design of oxygen-free copper tubes, thermally conductive insulation layers, and metal shielding layers, as well as the synergistic effects of the compounding of matrix epoxy resin and functional hyperbranched epoxy resin in the thermally conductive insulation layer, the construction of a three-dimensional thermally conductive filler network, and dynamic covalent cross-linking technology: (1) The out-of-plane thermal conductivity of the thermally conductive insulation layer is significantly improved. Through the synergistic design of dense filling of spherical alumina in the thermally conductive filler, in-plane thermal conductivity of sheet-like hexagonal boron nitride, and vertical orientation of boron nitride fibers along the thickness direction of the insulation layer, a low thermal resistance channel is constructed to connect the copper tube to the metal shielding layer. Combined with the rotational shearing orientation process, the out-of-plane thermal conductivity reaches more than 3.0 W / (m·K), which is 2 to 3 times higher than the traditional random-filled epoxy system, effectively reducing the operating temperature rise of the busbar.

[0026] (2) Excellent and stable electrical insulation performance; boron nitride filler has intrinsic insulation and low dielectric loss; epoxy group is designed with high cross-linking density, and the volume resistivity is greater than 1×10. 15 Ω·cm, power frequency breakdown strength greater than 20kV / mm, meeting the insulation safety requirements of medium and low voltage busbars.

[0027] (3) The flame retardant performance reaches V-0 level without sacrificing temperature resistance. The side chain of the functional hyperbranched epoxy resin introduces phosphorus-phenanthroline and triazine ring structures to achieve phosphorus-nitrogen synergistic flame retardancy. The rigid chain segments and intramolecular cavities of the hyperbranched molecules maintain high crosslinking density while toughening, which solves the contradiction that toughening inevitably reduces temperature resistance in traditional toughening and flame retardant modification.

[0028] (4) The copper-insulation layer exhibits high interfacial bonding strength and excellent thermal cycling reliability. The copper tube surface is treated with an aminosilane primer that undergoes controlled hydrolysis, forming Cu-O-Si chemical bonds. During the curing process of the insulation layer, the catechol side groups and boric acid undergo in-situ dehydration to form a 1,3,2-benzodioxaborane dynamic cross-linking structure. During the high-temperature stage of thermal cycling, the interfacial stress is reversibly released through BO bond exchange, and the structure is re-fixed after cooling. The initial copper bonding shear strength reaches over 14.5 MPa, and the retention rate is greater than 80% after 100 thermal cycles, with no debonding or cracking.

[0029] (5) The process is highly feasible and suitable for industrial production. It adopts a one-pot process of resin → filler pre-dispersion → low temperature feeding → rotary shear orientation → vacuum pre-curing in-situ esterification → step-curing. It can directly form a rigid insulating coating layer on the outer surface of the tubular busbar, with high production efficiency and good product consistency.

[0030] In summary, the epoxy insulation layer of the pure copper busbar described in this invention has the effects of high thermal conductivity, high insulation, high flame retardancy, high toughness and high interface reliability, which significantly reduces the operating temperature rise of the copper conductor and maintains the conductivity of the busbar system for a long time. This breaks through the bottleneck of existing busbar insulation technology, which makes it difficult to balance thermal conductivity and insulation, rigidity and toughness, and flame retardancy and temperature resistance. Attached Figure Description

[0031] Figure 1 Infrared spectra of DOPO-itaconic anhydride-catechol diamine adduct 1 and functional hyperbranched epoxy resin 1. Detailed Implementation

[0032] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0033] Unless otherwise specified, the experimental methods used in the embodiments are conventional methods, and the materials and reagents used are commercially available unless otherwise specified.

[0034] The raw materials used in the examples and comparative examples are described below: Oxygen-free copper: TU1 oxygen-free copper, oxygen content ≤10 ppm, conductivity 100~101% IACS.

[0035] Electrolytic copper: T2, copper content ≥99.90%, oxygen content 100~500 ppm, conductivity 98~100% IACS; Aluminum strip: After anodizing and KH-560 silane coupling agent primer treatment, the oxide film thickness is 5~15μm, and the aluminum strip thickness is 0.20mm; Matrix epoxy resin 1: Bisphenol A type epoxy resin, E-51, epoxy value 0.51mol / 100g; Matrix epoxy resin 2: Alicyclic epoxy resin, ERL-4221, epoxy value 0.72mol / 100g; Matrix epoxy resin 3: Phenolic epoxy resin, F-51, epoxy value 0.50~0.58mol / 100g; Boron nitride fiber: 12μm in diameter, 6mm in length, aspect ratio >10; Plate-shaped hexagonal boron nitride: Model RH-N, average diameter 10μm, treated with silane coupling agent KH-550, the amount of coupling agent is 1.0wt% of the filler mass; Spherical alumina: d50 diameter 5~20μm, treated with silane coupling agent KH-550, the amount of coupling agent is 1.0wt% of the filler mass; Silane coupling agent: 3-aminopropyltriethoxysilane, KH-550; Toughening agent 1: Core-shell rubber particles, MX-153, Kaneka; Toughening agent 2: Carboxyl-terminated hyperbranched polyester, HyPer C101, Wuhan Hyperbranched Resin Technology; Trifunctional epoxy monomer 1: triglycidyl isocyanurate; Trifunctional epoxy monomer 2: Trimethylolpropane triglycidyl ether; DOPO-itaconic anhydride-catechol diamine adduct 1: (1) 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) was reacted with itaconic anhydride to prepare DOPO-itaconic anhydride intermediate: 0.5 mol DOPO and 0.5 mol itaconic anhydride were dissolved in 500 mL anhydrous THF and stirred until the solid was completely dissolved; after nitrogen purging 3 times, the temperature was raised to 50~80℃ under nitrogen protection and refluxed for 6 h; after the reaction was completed, THF was removed by rotary evaporation to obtain crude product; washed 3 times with anhydrous ethanol and dried under vacuum at 50℃ for 12 h to obtain intermediate DOPO-ITA with a yield of 85%.

[0036] (2) Catechol diamine 1 was prepared by Schiff base condensation and sodium borohydride reduction of 3,4-dihydroxybenzaldehyde and ethylenediamine: 2.0 mol of 3,4-dihydroxybenzaldehyde was dissolved in 200 mL of anhydrous ethanol, 1.0 mol of ethylenediamine was added, and the reaction was carried out at 40 °C for 3 h under nitrogen protection; the temperature was lowered to 0 °C, 4.0 mol of NaBH4 was added in batches, and the reaction was carried out at room temperature for 6 h; the reaction was quenched with dilute hydrochloric acid, extracted with ethyl acetate, and recrystallized to obtain the product with a yield of 82%.

[0037] (3) The DOPO-itaconic anhydride intermediate and catechol diamine were amidated and condensed to obtain the DOPO-itaconic anhydride-catechol diamine adduct: 0.2 mol of DOPO-itaconic anhydride and 0.1 mol of catechol diamine were dissolved in 200 mL of anhydrous DMSO, and the mixture was stirred and purged with nitrogen three times. The temperature was raised to 100 °C under nitrogen protection and the reaction was stirred continuously for 24 h. After the reaction was completed, the mixture was cooled to room temperature and the reaction solution was slowly poured into 500 mL of deionized water to precipitate the precipitate. The precipitate was filtered, washed three times with deionized water, and then washed twice with anhydrous ethanol. The mixture was dried under vacuum at 50 °C for 12 h to obtain DOPO-itaconic anhydride-catechol diamine adduct 1 with a yield of 63%.

[0038] DOPO-itaconic anhydride-catechol diamine adduct 2: Compared with DOPO-itaconic anhydride-catechol diamine adduct 1, the difference is that step (2) is to prepare catechol diamine 2 by Schiff base condensation and sodium borohydride reduction of 3,4-dihydroxybenzaldehyde and 1,4-diaminobutane: 2.1 mol protocatechuic aldehyde was dissolved in a mixed solvent of 150 mL anhydrous ethanol and 50 mL THF, 1.0 mol 1,4-diaminobutane was added, and the reaction was carried out at 50 °C for 4 h under nitrogen protection; the temperature was lowered to 0 °C, 4.5 mol NaBH4 was added in batches, and the reaction was carried out at room temperature for 7 h; saturated ammonium chloride was used for quenching, dichloromethane was used for extraction, and methanol / water was used for recrystallization, with a yield of 78%.

[0039] DOPO-itaconic anhydride-catechol diamine adduct 3: Compared with DOPO-itaconic anhydride-catechol diamine adduct 1, the difference is that step (2) is to prepare catechol diamine 3 by Schiff base condensation and sodium borohydride reduction of 3,4-dihydroxybenzaldehyde and 1,6-diaminohexane: 2.2 mol protocatechuic aldehyde was dissolved in 100 mL methanol and 100 mL THF mixed solvent, 1.0 mol 1,6-diaminohexane was added, and the reaction was carried out at 55 °C for 5 h under nitrogen protection; the temperature was lowered to 0 °C, 5.0 mol NaBH4 was added in batches, and the reaction was carried out at room temperature for 8 h; saturated ammonium chloride was used for quenching, dichloromethane was extracted, and column chromatography was used for purification (petroleum ether / ethyl acetate / triethylamine), with a yield of 71%.

[0040] Functional hyperbranched epoxy resin 1: 0.1 mol of DOPO-itaconic anhydride-catechol diamine adduct 1, 0.11 mol of trifunctional epoxy monomer 1 (triglycidyl isocyanurate) and 0.1 g of triphenylphosphine were added to 100 mL of anhydrous DMSO. The mixture was stirred and purged with nitrogen three times. The temperature was raised to 115 °C and the reaction was carried out under nitrogen protection for 12 h. After the reaction was completed, the mixture was cooled to room temperature and the reaction solution was slowly poured into 100 mL of deionized water to precipitate the precipitate. The precipitate was filtered, washed three times with deionized water and twice with anhydrous ethanol, and dried under vacuum at 50 °C for 12 h to obtain functional hyperbranched epoxy resin 1 with a yield of 81%.

[0041] Functional hyperbranched epoxy resin 2: Compared with functional hyperbranched epoxy resin 1, the difference is that DOPO-itaconic anhydride-catechol diamine adduct 1 is replaced with DOPO-itaconic anhydride-catechol diamine adduct 2.

[0042] Functional hyperbranched epoxy resin 3: Compared with functional hyperbranched epoxy resin 1, the difference is that DOPO-itaconic anhydride-catechol diamine adduct 1 is replaced with DOPO-itaconic anhydride-catechol diamine adduct 3.

[0043] Functional hyperbranched epoxy resin 4: Compared with functional hyperbranched epoxy resin 1, the difference is that trifunctional epoxy monomer 1 (triglycidyl isocyanurate) is replaced with trifunctional epoxy monomer 2 (trimethylolpropane triglycidyl ether).

[0044] The DOPO-itaconic anhydride-catechol diamine adduct 1 and the functional hyperbranched epoxy resin 1 were measured using a Nicolet iS 50 Fourier transform infrared spectrometer (USA) at a resolution of 4 cm⁻¹. -1 The scanning range is 4000~500cm. -1 The result is as follows Figure 1 As shown.

[0045] The main absorption peaks of DOPO-itaconic anhydride-catechol diamine adduct 1 are assigned as follows: 3380cm -1 The nearby broad absorption band is attributed to the superposition of the OH stretching vibration and the NH stretching vibration of the amide in the catechol structure, proving that catechol diamine has been successfully introduced. 2920cm -1 2850cm -1 : Methylene CH stretching vibration (from the ethylenediamine backbone and itaconic anhydride segment); 1718cm -1 The C=O stretching vibration in the carboxyl / amide group proves that the carboxyl / anhydride structure of the DOPO-itaconic anhydride intermediate is still retained in the carbonyl form after amidation. 1625cm -1 : Amide NH bending vibration or aromatic ring skeleton vibration; 1600cm -1 1510cm -1 The stretching vibration of the C=C skeleton of the catechol benzene ring confirmed that the 1,2-disubstituted benzene ring structure exists in the molecular side chain. 1280cm -1 : Phenol CO stretching vibration (characteristic of catechol); 1190cm -1 The P=O stretching vibration in the phosphaphenanthrene structure; 750cm -1 : Out-of-plane bending vibration of aromatic ring CH.

[0046] The assignments of the main absorption peaks of functional hyperbranched epoxy resin 1 and their changes compared with those of DOPO-itaconic anhydride-catechol diamine adduct 1 are as follows: 3385cm -1The significantly broadened and enhanced strong absorption band in the vicinity is due to the superposition of the phenolic hydroxyl OH of catechol and the large number of secondary hydroxyl OH generated after the ring opening of epoxy. The peak shape is significantly broader than that of DOPO-itaconic anhydride-catechol diamine adduct 1, which proves that the epoxy ring opening generates abundant terminal hydroxyl groups during hyperbranching polymerization. 1735cm -1 The carbonyl C=O stretching vibration of the ester group. Compared to the DOPO-itaconic anhydride-catechol diamine adduct 1, which has a stretching vibration of 1718 cm⁻¹. -1 The C=O peak of the carboxyl group shifted to a higher wavenumber and weakened, proving that the terminal carboxyl group of DOPO-itaconic anhydride-catechol diamine adduct 1 underwent a ring-opening esterification reaction with the epoxy group of TGIC, forming a hyperbranched skeleton linked by ester bonds. 1690cm -1 Nearby: C=O or CN vibrations in the isocyanurate ring (from the TGIC triazine ring skeleton); 1600cm -1 1510cm -1 The preservation of the aromatic ring skeleton vibration proves that the catechol and phenanthrene structures were not destroyed during the polymerization process; 1458cm -1 CH bending vibration; 1260cm -1 : Phenol CO stretching vibration (catechol side chain retention); 1100-1030cm -1 The COC stretching vibration of the ether bond is a characteristic of the ether bond network formed after the ring opening of the epoxy group; 915cm -1 The characteristic absorption peaks of terminal epoxy groups indicate that there are still terminal epoxy groups remaining after TGIC participates in polymerization, which can be used as crosslinking points for subsequent curing reactions. 750cm -1 : Out-of-plane bending vibration of aromatic ring CH.

[0047] Dynamic crosslinking agent 1: Phenylated boric acid, commercially available; Dynamic crosslinking agent 2: Boric acid, commercially available; Curing agent: Methylhexahydrophthalic anhydride, commercially available; Curing accelerator: 2-ethyl-4-methylimidazole, commercially available.

[0048] Additives: Reactive diluent, 1,4-Butanediol diglycidyl ether Unless otherwise specified, all components and raw materials used in the embodiments and comparative examples of this invention are commercially available, and the same type of components and raw materials are used in each parallel experiment.

[0049] Examples and Comparative Examples A high-conductivity pure copper busbar includes an oxygen-free copper tube, a thermally conductive insulating layer covering the outer surface of the oxygen-free copper tube, and a metal shielding layer covering the outer surface of the thermally conductive insulating layer. The oxygen-free copper tube has a wall thickness of 3 mm, a diameter of 220 mm, and a current carrying capacity of 5000 A. The metal shielding layer is made of spirally wrapped aluminum strip with a thickness of 0.2 mm. The thermally conductive insulating layer has a formulation as shown in Table 1 and a thickness of 4 mm. The preparation method of the high-conductivity pure copper busbar is as follows: S1. The oxygen-free copper tube is dry-blasted with 60-mesh quartz sand to roughen the surface to a surface roughness of ≤1.6μm and remove oxide scale. It is then immersed in 60℃ alkaline cleaning solution (sodium carbonate 15g / L + sodium phosphate 10g / L + surfactant 2g / L) and ultrasonically cleaned for 10min to remove oil stains. Clean compressed air is then blown out, followed by ultrasonic cleaning in anhydrous ethanol for 5min. Nitrogen gas is then blown dry. The tube is then immersed in aminosilane coupling agent KH-550 in ethanol and aqueous solution (ethanol / water = 95 / 5 (v / v)) at a concentration of 1.5wt%. The pH is adjusted to 4.5~5.0 with acetic acid. The tube is left to stand at room temperature for 30min. After removal, it is dried at 120℃ for 30min to form a chemically bonded base coating. S2. Weigh the base epoxy resin, functional hyperbranched epoxy resin, thermally conductive filler and toughening agent according to the weight parts, put them into a mixer, heat to 70℃, vacuum to ≤-0.09MPa, disperse at high speed of 1200rpm for 30min to make the filler uniformly wetted and pre-dispersed in the resin matrix; cool to 40℃, add curing agent, curing accelerator and dynamic crosslinking agent in sequence under continuous stirring, stir at low speed for 10min until dispersed, vacuum degas for 10min to obtain thermally conductive insulating layer adhesive; S3. Immerse the oxygen-free copper tube obtained in S1 into a thermally conductive insulating layer adhesive bath, ensuring the adhesive evenly coats the outer surface of the copper tube. Place the coated copper tube into a stainless steel molding mold, and position the mold horizontally. Rotate at 15 rpm for 60 minutes. Under the coupling effect of the rotating shear field and weak centrifugal force, the thermally conductive filler is oriented along the radial-circumferential composite direction within the insulating layer. This, combined with the in-plane thermally conductive phase of the plate-like hexagonal boron nitride and the densely packed phase of the spherical alumina, constructs a three-dimensional low thermal resistance thermally conductive channel penetrating from the outer surface of the copper tube to the inner surface of the metal shielding layer. Subsequently, place the mold at 90℃ and ≤-0.0℃. Pre-curing and in-situ dehydration and esterification were carried out under 95 MPa conditions for 3 hours. During this stage, the epoxy-anhydride system reacted slowly, while the catechol groups of the functional hyperbranched epoxy resin side chain and phenylboronic acid under vacuum dehydration drove a condensation reaction to form a 1,3,2-benzodioxaborane structure in situ. The water generated by the reaction was continuously removed, which pushed the borate ester cyclization equilibrium to the right. The vacuum was released, and the mold was transferred to 120℃ for curing for 2 hours. Then it was cured at 150℃ for 2 hours until it was completely cured. After natural cooling to ≤40℃, it was demolded to obtain an oxygen-free copper tube with a thermally conductive and insulating layer. S4. On the outer surface of the thermally conductive insulation layer, aluminum strip is spirally wrapped, and the inner metal surface is pre-coated with epoxy silane coupling agent. The overlap width is ≥5mm, the spiral angle is 20°, and the overlap is fixed with silver-filled epoxy conductive adhesive at intervals of ≤1.5m and with a cross-sectional area ≥4mm². 2 The tinned copper braided wire is used as the grounding lead. One end is reliably connected to the metal shielding layer at the overlap point through a crimp terminal or argon arc spot welding, and the other end is led out to the system protective ground bus to ensure that the metal shielding layer is at zero potential.

[0050] Table 1. Specific composition and proportions (parts by weight) of thermally conductive and insulating layer materials.

[0051] Comparative Example 3 The difference from Example 2 is that the oxygen-free copper tube is replaced with an electrolytic copper tube.

[0052] The thermally conductive insulating layers and busbars prepared in the examples and comparative examples were subjected to the following performance tests, and the results are shown in Table 2.

[0053] (1) Out-of-plane thermal conductivity: The test was conducted according to ASTM D5470-17, using the steady-state heat flow method. The thermally conductive insulating layer was pre-cured in a stainless steel mold at 90℃ and ≤-0.095MPa for 3 hours, and then cured at 150℃ for 2 hours to prepare a sample with a diameter of Φ25mm±0.5mm and a thickness of 4mm. The upper and lower surfaces were sanded to a roughness Ra≤1.6μm. The sample was placed between the heating block and cooling block of the LW-9389 interface material thermal resistance and thermal conductivity measuring instrument, and a contact pressure of 0.5MPa was applied. The test temperature was 25℃±2℃. After the heat flow and temperature difference reached a steady state (the fluctuation of the readings was <1% for 3 consecutive readings), the hot end temperature Th, the cold end temperature Tc, the heat flux density Q, and the sample thickness L were recorded. The out-of-plane thermal conductivity κ was calculated according to the formula κ=Q×L / [A×(Th-Tc)], where A is the effective test area.

[0054] (2) Volume resistivity: Tested according to GB / T 31838.2-2019. The cured insulation layer was made into a circular sheet with a diameter of Φ100mm and a thickness of 4mm, and the surface was cleaned and dried. A ZC-90G high insulation resistance measuring instrument was used, with a test voltage of 500VDC and a charging time of 300s. A three-electrode system was used (the main electrode diameter was Φ50mm, and the gap between the protective electrodes was 2mm). The test was conducted at a temperature of 23℃±2℃ and a relative humidity of 50%±5%. The stable volume resistivity value Rv was read, and the volume resistivity was calculated according to the formula ρv=Rv×A / t, where A is the effective area of ​​the main electrode and t is the thickness of the sample. The average value of 5 test points was taken.

[0055] (3) Power frequency breakdown strength: The test was conducted in accordance with GB / T 1408.1-2016. The cured insulation layer was made into a circular disc with a diameter of Φ100mm and a thickness of 4mm. A 50kV power frequency breakdown tester was used, with Φ25mm brass cylindrical electrodes, a chamfer radius of 3mm at the electrode edge, a voltage ramp rate of 3.0kV / s, and transformer oil as the dielectric. The breakdown voltage Ub was recorded, and the breakdown strength was calculated according to Eb=Ub / d, where d is the measured thickness at the breakdown point. Five samples were tested in each group, and the average value was taken after removing outliers that deviated from the average value by ±20%.

[0056] (4) Bending strength: The test was conducted in accordance with GB / T 9341-2008. The cured insulation layer was made into a sample with a size of 80mm×10mm×4mm. A universal testing machine was used with a span of 64mm and a head descent rate of 2mm / min. The test was conducted at an environment of 23℃±2℃. The average value of 5 samples was taken.

[0057] (5) Elongation at break: The test was conducted in accordance with GB / T 528-2009. The cured insulation layer was cut into dumbbell I-shaped specimens (total length 115 mm, narrow section width 6 mm, narrow section length 25 mm), and tested using an electronic universal testing machine at a tensile rate of 500 mm / min at an environment of 23℃±2℃. The average value of 5 specimens was taken.

[0058] (6) Copper bond shear strength: Tested according to ASTM D1002. The lap shear method was used. TU1 oxygen-free copper sheets (with the same surface treatment as S1) were cut into 100mm×25mm×2mm pieces with an overlap length of 12.5mm. The adhesive layer thickness was controlled at 0.2~0.3mm (controlled by gaskets). Tension was performed on a universal testing machine at a rate of 1.3mm / min. Five samples were tested and the average value was taken.

[0059] (7) Bond retention rate after thermal cycling: The lap shear test specimens prepared according to ASTM D1002 were placed in a high and low temperature alternating test chamber and subjected to thermal cycling according to the following procedure: Low temperature section: -40℃, hold for 30 min; Heating section: increase to 150℃ at 5℃ / min; High temperature section: 150℃, hold for 30 min; Cooling section: decrease to -40℃ at 5℃ / min. The above constitutes one cycle, and a total of 100 cycles were performed. After the cycle, the specimens were allowed to stand for 24 h at 23℃±2℃, and then the copper bond shear strength was tested according to ASTM D1002. The average value of 5 specimens was taken.

[0060] (8) Flame retardancy rating test (UL-94): The thermally conductive insulating layer adhesive is poured into a stainless steel mold, and the sample size is 125mm×13mm×4mm. The UL-94 vertical burning tester is used to test according to the UL-94 standard, and it is observed whether there are molten drips that ignite the degreased cotton. Five samples are tested in each group, and the worst result is used for rating.

[0061] (9) Overall busbar temperature rise test: Take a 1.0m long busbar section and install it horizontally on the temperature rise test bracket. Connect both ends of the sample to the low-voltage high-current generator through copper busbars. Under the conditions of ambient temperature 20℃±5℃ and natural convection, apply a rated current of 5000A (AC, 50Hz). After the temperature reaches a steady state, use a K-type thermocouple (accuracy ±1℃) to measure the temperature at the following locations: T1: outer surface of copper tube (close to the inner surface of the insulation layer, pre-embedded in the S3 covering stage); T2: outer surface of metal shielding layer; T0: ambient temperature (1m away from the sample). Calculate the temperature rise of each part: ΔT=T-T0.

[0062] (10) Busbar conductivity and long-term attenuation test: Initial conductivity: The busbar section is placed in a constant temperature environment of 20℃±1℃ for no less than 4 hours, and the DC resistance R of the busbar is measured by the double-arm bridge method. 20 (Measurement length 1.0m, deduct end contact resistance), according to the formula Convert to %IACS, where L=1.0m, A is the cross-sectional area of ​​the copper tube, and ρIACS=1.7241×10 -8 Ω·m. Operating conductivity: A 1000-hour long-term aging test was conducted (5000A rated current, 1000 hours of cumulative operation, with intermittent shutdowns for inspection allowed during the period). After aging, the resistance R was remeasured at 20℃. 20 ', calculate the conductivity attenuation rate η=(σ 20 -σ 20 ′) / σ 20 ×100%.

[0063] Table 2 Performance test results of the examples and comparative examples

[0064] In Example 2, spherical fillers create a dense framework, sheet-like fillers provide in-plane thermal bridging, and fibers, oriented vertically in a rotating shear field, construct radial thermal bridges. These three elements synergistically form a low-thermal-resistance three-dimensional network. The intramolecular cavities of the hyperbranched epoxy resin absorb impact energy, achieving toughening, while rigid phosphaphenanthrene / triazine segments maintain high crosslinking density and temperature resistance. A silane undercoat on the copper tube surface forms chemical bonds, while the cyclic borate ester formed by the in-situ dehydration of side-chain catechols and boric acid releases interfacial stress through reversible BO bond exchange during high-temperature thermal cycling, and then re-fixes upon cooling, achieving adaptive interface reconstruction. Examples 3 and 4 moderately lengthen the alkyl chains in the hyperbranched framework, increasing the proportion of flexible methylene segments and enhancing molecular chain mobility, thus improving toughening. However, the rigidity of the crosslinked network slightly decreases; the increased spacing between catechol side groups relatively reduces the dynamic borate ester bond density, slightly weakening the interfacial stress release efficiency. Example 5 uses trifunctional epoxy monomers with different structures to construct a hyperbranched framework. Since the functionality is the same, an equivalent hyperbranched topology can still be formed; however, the new monomers do not contain rigid triazine rings, resulting in slightly weaker crosslinking network rigidity and a slight decrease in temperature resistance, while the flexible ether bonds slightly improve interfacial stress adaptability. In Comparative Example 1, the hyperbranched epoxy resin lacking functionality exhibits severe agglomeration of high-volume-fraction fillers in a single matrix, a significant increase in filler-resin interface defects, thermal network breakage, and the formation of water vapor permeation channels and electric field concentration points. The absence of phosphorus / nitrogen flame-retardant structure, dynamic crosslinking precursors, and hyperbranching toughening synergy leads to comprehensive deterioration in mechanical properties, temperature resistance, and interfacial reliability; the static rigid interface undergoes large-area debonding under thermal stress. Comparative Example 2, lacking only a dynamic crosslinking agent, does not affect the intrinsic thermal conductivity, dispersion, toughening, and flame-retardant properties of the insulation layer; however, the catechol side groups cannot form cyclic borate ester dynamic bonds, resulting in a static rigid bond at the interface. The CTE mismatch between copper and epoxy generates cumulative shear stress during thermal cycling. The static interface cannot adaptively release this stress, ultimately leading to microcrack initiation and interface debonding. Comparative Example 3 uses electrolytic copper with a higher oxygen content instead of oxygen-free copper. Its surface oxide layer is significantly thicker and more porous, making it difficult for the silane coupling agent to form uniform and dense chemical bonds, resulting in a decrease in initial interfacial bond strength. During thermal cycling, copper continues to oxidize, and the volume expansion of the oxide generates additional compressive stress at the interface. This stress, combined with the CTE mismatch, accelerates interface failure. Simultaneously, the copper conductor's resistance increases due to oxidation, creating a vicious cycle of heating and oxidation.

[0065] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A high-conductivity pure copper busbar, characterized in that, The system comprises an oxygen-free copper tube, a thermally conductive insulating layer covering the outer surface of the oxygen-free copper tube, and a metal shielding layer covering the outer surface of the thermally conductive insulating layer. The thermally conductive insulating layer, by weight, comprises 75-100 parts of a matrix epoxy resin, 10-15 parts of a functional hyperbranched epoxy resin, 90-130 parts of a thermally conductive filler, 8-13 parts of a toughening agent, 1.5-4 parts of a dynamic crosslinking agent, 80-100 parts of a curing agent, 0.3-0.8 parts of a curing accelerator, and auxiliary agents. 0-6 parts of the agent; the functional hyperbranched epoxy resin is prepared by A2+B3 polymerization reaction of DOPO-itaconic anhydride-catechol diamine adduct and trifunctional epoxy monomer, wherein the trifunctional epoxy monomer is selected from one or more of triglycidyl isocyanurate, trimethylolpropane triglycidyl ether, and tris(4-hydroxyphenyl)methane triglycidyl ether; the DOPO-itaconic anhydride-catechol diamine adduct has the following general structural formula: Where n is a natural number between 1 and 3; The toughening agent comprises one or more of core-shell rubber particles or terminal carboxyl hyperbranched polyester; the dynamic crosslinking agent comprises one or more of boric acid, phenylboronic acid, or 3-carboxyphenylboronic acid; the curing agent is methylhexahydrophthalic anhydride; the curing accelerator is 2-ethyl-4-methylimidazolium; the additives comprise one or more of defoamers or reactive diluents; the thermally conductive filler comprises a compound of boron nitride fibers, sheet-like hexagonal boron nitride, and spherical alumina, wherein the spherical alumina is densely packed, the sheet-like hexagonal boron nitride is in-plane thermally conductive, and the boron nitride fibers are perpendicularly oriented along the thickness direction of the insulation layer; the mass ratio of boron nitride fibers, sheet-like hexagonal boron nitride, and spherical alumina is (1~2):(2~3):(6~8).

2. The high conductivity pure copper busbar as described in claim 1, characterized in that, The oxygen-free copper tube is made of oxygen-free copper with an oxygen content of no more than 20 ppm and a conductivity of no less than 99% IACS, and the wall thickness of the oxygen-free copper tube is 2~5 mm.

3. The high conductivity pure copper busbar as described in claim 1, characterized in that, The material of the metal shielding layer is at least one of aluminum and aluminum alloys, austenitic stainless steel, and copper-clad aluminum composite materials, and the thickness of the metal shielding layer is 0.1~0.5mm.

4. The high conductivity pure copper busbar as described in claim 1, characterized in that, The thickness of the thermally conductive insulating layer is 2~8mm.

5. The high conductivity pure copper busbar as described in claim 1, characterized in that, The matrix epoxy resin is selected from one or more of bisphenol A type epoxy resin, alicyclic epoxy resin, and phenolic epoxy resin.

6. The high conductivity pure copper busbar as described in claim 1, characterized in that, The preparation method of the DOPO-itaconic anhydride-catechol diamine adduct includes the following steps: (1) DOPO-itaconic anhydride intermediate was prepared by reacting 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide with itaconic anhydride; (2) Catechol diamine was prepared by Schiff base condensation and sodium borohydride reduction of 3,4-dihydroxybenzaldehyde and C2~C6 aliphatic diamine. (3) The DOPO-itaconic anhydride intermediate and catechol diamine were amidated and condensed to obtain the DOPO-itaconic anhydride-catechol diamine adduct.

7. The method for preparing a high-conductivity pure copper busbar according to any one of claims 1 to 6, characterized in that, Includes the following steps: S1. Roughen the surface of the oxygen-free copper tube to remove oxide scale and oil stains, then immerse it in an aqueous solution of aminosilane coupling agent ethanol, adjust the pH to 4.5~5.0 with acetic acid, let it stand at room temperature for a period of time, take it out and dry it to form a chemically bonded base coating. S2. Weigh the base epoxy resin, functional hyperbranched epoxy resin, thermally conductive filler and toughening agent according to the weight parts, put them into a mixer, heat to 60~80℃, vacuum, and disperse at high speed to make the filler uniformly wet and pre-disperse in the resin matrix; cool to 40~50℃, add curing agent, curing accelerator and dynamic crosslinking agent in sequence under continuous stirring, stir at low speed until dispersed, vacuum degas, and obtain thermally conductive insulating layer adhesive. S3. Immerse the oxygen-free copper tube obtained in S1 into the thermally conductive insulating layer adhesive tank, so that the adhesive is evenly coated on the outer surface of the copper tube. Put the coated copper tube into a stainless steel forming mold, place the mold horizontally, and rotate it at low speed to make the thermally conductive filler oriented in the insulating layer along the radial-circumferential composite direction. Then, place the mold under 80~100℃ and ≤-0.095 MPa conditions for pre-curing and in-situ dehydration and esterification. Release the vacuum, transfer the mold to 120~150℃ conditions for complete curing, and demold naturally to obtain the oxygen-free copper tube coated with the thermally conductive insulating layer. S4. On the outer surface of the thermally conductive insulation layer, a metal strip is spirally wrapped or a metal foil is longitudinally wrapped. The overlap is made of conductive adhesive or argon arc spot welding, and a grounding wire is led out at a spacing of ≤1.5m to be reliably connected to the system protective ground.

Citation Information

Patent Citations

  • High-thermal-conductivity and low-viscosity epoxy pouring sealant and preparation method thereof

    CN117363287A

  • High-efficiency heat dissipation bus

    CN120699435A